An Atypical Case of Meckel's Diverticulum Assessed by SPECT/CT Imaging. (12th April 2022) - Mittl, Gregory S.; Servaes, Sabah-e-Noor; Zhuang, Hongming
Abstract: A 17-year-old adolescent boy presented with multiple episodes of hematochezia. After a negative 99m TcO4 scan, upper endoscopy, colonoscopy, and CT angiography, the patient underwent a second 99m TcO4 scan with ranitidine. The anterior images demonstrated a faint, delayed focus of uptake in the midabdomen without correlate on lateral projections. SPECT/CT was performed for localization with the focus of activity seen in an anterior loop of distal small bowel adjacent to the umbilicus. The patient subsequently underwent diagnostic laparoscopy and resection of the diverticulum with postoperative resolution of the symptoms.